Giant Recanalized Paraumbilical Vein Mimicking Paraumbilical Hernia-Cruveilhier-Baumgarten Syndrome - Mehra, Alankrita; Roshan, Rakesh; Raghuvanshi, Sameer (International Journal of Medical Research and Review, 2015)
Recanalized paraumbilical vein is rare but important cause of paraumbilical non pulsatile mass. We report a case of giant recanalized paraumbilical vein in known case of cirrhotic liver disease and portal hypertension mimicking as paraumbilical hernia on clinical examination.B –mode and Doppler study pointed towards the subcutaneous tortuous dilated tubular structure at paraumbilical region showing color flow and extension upto liver surface in parietal wall of abdomen. Venous blood flow demonstrated on color Doppler study. CT study used to make final diagnosis which demonstrated subcutaneous dilated tortuous opacified tubular veins at paraumbilical region extending along the parietal wall of abdomen into hepatic fissure to join portal vein